2005
DOI: 10.1002/mus.20387
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological testing in anorectal disorders

Abstract: The neurophysiological techniques currently available to evaluate anorectal disorders include concentric needle electromyography (EMG) of the external anal sphincter, anal nerve terminal motor latency (TML) measurement in response to transrectal electrical stimulation or sacral magnetic stimulation, motor evoked potentials (MEPs) of the anal sphincter to transcranial magnetic cortical stimulation, cortical recording of somatosensory evoked potentials (SEPs) to anal nerve stimulation, quantification of electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 173 publications
(196 reference statements)
0
40
1
2
Order By: Relevance
“…Nerves of the anoscrotal junction has been one of major interests of researchers because they should contain an afferent route for autonomic nerve reflexes in the pelvic floor involving the urinary and anal sphincter functions (Bird and Hanno, 1998;Lefaucheur, 2006;Yilmaz et al, 2009;Hotta et al, 2012). The posterior part of the human scrotum is innervated by a branch of the pudendal nerve, i.e., the posterior scrotal nerve.…”
Section: Introductionmentioning
confidence: 99%
“…Nerves of the anoscrotal junction has been one of major interests of researchers because they should contain an afferent route for autonomic nerve reflexes in the pelvic floor involving the urinary and anal sphincter functions (Bird and Hanno, 1998;Lefaucheur, 2006;Yilmaz et al, 2009;Hotta et al, 2012). The posterior part of the human scrotum is innervated by a branch of the pudendal nerve, i.e., the posterior scrotal nerve.…”
Section: Introductionmentioning
confidence: 99%
“…Although clinical neurophysiology is practiced in almost all neurology departments, pelvic floor neurophysiology requires specific knowledge about neurophysiological techniques and a sound anatomo-clinical background (Fowler et al, 2002). A number of relevant critical reviews discuss the methodological aspects and diagnostic value of neurophysiological tests in pelvic floor disease (Fowler et al, 2002;Vodusek, 2005;Lefaucheur, 2006), but the actual clinical usefulness of these tests is not yet completely clarified. We performed a systematic literature review to provide clinicians with evidence-based recommendations on the use of neurophysiological tests in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in other clinical scenarios, for example in the presence of syndromes or symptoms having a different etiology or pathogenetic mechanism (e.g., 'generic' urgency or urinary retention, fecal incontinence or constipation, and pelvic pain), or when no clearly defined independent a priori criteria for the 'neurogenic' origin of the symptoms are met, the pathogenetic relevance of an altered test result can often only be assumed. Most of the literature reviews on pelvic floor neurophysiology published to date suggest recommendations on the clinical use of diagnostic tests that are based on expert opinion (Olsen and Rao, 2001;Lefaucheur, 2006;Podnar, 2007). However, a systematic literature analysis involving a selection of the most relevant studies and evaluation of their methodological quality is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…PNTML is reported to be a fairly reproducible but inherently insensitive measure of neuropathy. 25,26 The ICI-CDT has concluded that, like other neuro-electrophysiological testing, PNTML shows substantially different published ''cut-off'' values to discriminate normal from abnormal. This demonstrates that PNTML is operator and laboratory dependent.…”
Section: Tests Related To Primary Fecal Incontinencementioning
confidence: 99%